2017
DOI: 10.3168/jds.2017-12732
|View full text |Cite
|
Sign up to set email alerts
|

Genotype imputation in a tropical crossbred dairy cattle population

Abstract: The objective of this study was to investigate different strategies for genotype imputation in a population of crossbred Girolando (Gyr × Holstein) dairy cattle. The data set consisted of 478 Girolando, 583 Gyr, and 1,198 Holstein sires genotyped at high density with the Illumina BovineHD (Illumina, San Diego, CA) panel, which includes ∼777K markers. The accuracy of imputation from low (20K) and medium densities (50K and 70K) to the HD panel density and from low to 50K density were investigated. Seven scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…A total of 6,760 animals were genotyped using different SNP chip densities: 4,403 Girolando cattle genotyped with the Illumina Bovine SNP50 BeadChip v. 2 (50K; Illumina, San Diego, CA), and 1,256 Holstein, 624 Gir, and 477 Girolando cattle genotyped at high density with the Illumina Bovine HD BeadChip (777K). Genotypes generated with 20K, 50K, or 70K chips were imputed to the HD v. 2 panel using FImpute software (Sargolzaei et al, 2014) with the default parameter settings and using pedigree information (Oliveira Júnior et al, 2017). In total, 413K SNP were imputed.…”
Section: Genotyping and Quality Controlmentioning
confidence: 99%
“…A total of 6,760 animals were genotyped using different SNP chip densities: 4,403 Girolando cattle genotyped with the Illumina Bovine SNP50 BeadChip v. 2 (50K; Illumina, San Diego, CA), and 1,256 Holstein, 624 Gir, and 477 Girolando cattle genotyped at high density with the Illumina Bovine HD BeadChip (777K). Genotypes generated with 20K, 50K, or 70K chips were imputed to the HD v. 2 panel using FImpute software (Sargolzaei et al, 2014) with the default parameter settings and using pedigree information (Oliveira Júnior et al, 2017). In total, 413K SNP were imputed.…”
Section: Genotyping and Quality Controlmentioning
confidence: 99%
“…In this study, we analyzed the relationships between sperm cell velocities and semen seminal plasma contents in Capoeta trutta. Thereby, the values of VSL, VCL, and VAP were higher than those for Barbus sharpeyi, Catla catla, and Labeo rohita (Kalbassi et al, 2013); they were similar to Labeo calbasu, Cirrhinus mrigala, Hypophthalmichthys molitrix, and Ctenopharyngodon idella (Verma et al, 2009). However, the sperm cell density of Capoeta trutta (9.44 × 10 9 ) was found to be more than the sperm cell density of Liza abu (4.27×10 9 ) (Şahinöz et al, 2008) and Capoeta damascina (∼ 5 × 10 9 ) (Zadmajid et al, 2018), while it was found to be less for Barbus grypus (18.8 × 10 9 ) (Khodadadi et al, 2016), Cyprinus carpio (16.96-18.81 × 10 9 ) (Cejko et al, 2014), and Ctenopharyngodon idella (15.43 × 10 9 ) (Bozkurt et al, 2008).…”
Section: Discussionmentioning
confidence: 63%
“…Another factor that affected the imputation error rate was the difference in MAF, which at first sight may be an unexpected indicator for imputation, especially since haplotypes are used for imputation. However, as shown in other studies (Huang et al, 2009;Oliveira Júnior et al, 2017), since the process of imputation first calculated correlation between reference and target haplotypes and then considered the consistency between the haplotypes, when imputing markers with a higher allele frequency can maintain high correlations, if the frequency between the two genotypes were similar, the marker may not be imputed correctly.…”
Section: Discussionmentioning
confidence: 99%